Ghost Criminology: a Framework for the Discipline’s Spectral Turn - Fiddler, Michael (The British journal of criminology, 2024)
Drawing upon recent criminological scholarship examining spectrality, as well as Jacques Derrida’s notion of hauntology, this article sets out a framework to explore harms experienced as ‘out of joint’. We propose a new sub-discipline of ‘ghost criminology’ as a means to explore and reckon with these afterlives. We identify three strands of the (in)visible, the (in)corporeal and dead space with which to capture phenomena hovering between presence and absence. In doing so, we provide examples of justice being achieved within this sense of time being ‘off its hinges’. A ‘ghost criminology’ provides a means of listening to the voices of the discipline’s dead, as well as the ghosts of its future.